Efeitos abióticos na composição do óleo essencial de Lippia gracilis: influência na mortalidade e repelência de Sitophilus zeamais - Souza, Felipe Hermínio Oliveira (2013)
Abiotic factors may interfere in production of plant secondary metabolites and consequently influence the bioactivity of these compounds on insect pests. Thus, this study aimed to evaluate the influence of different agricultural practices (irrigation, mineral fertilizer and organic manure) in chemical composition of the essential oil (EO) of Lippia gracilis and its effects on the maize weevil Sitophilus zeamais.The chemical compositions of EO from plants of L. gracilis cultured on different treatments were analyzed using GC-MS and GC-FID. The carvacrol was the major component of EO in different agricultural practices followed by thymol and ñ-cymene.These three monoterpenes were used in subsequent bioassays. Cultivation practices did not significantly affect the composition of the OEs of L. gracilis. However, small variations in the composition of EOs resulted in different biological responses to S. zeamais. All EOs of L. gracilis and its main monoterpenes applied topically showed low toxicity on S. zeamais after 84 hours exposure at a dose 10 mg g-1. However, these same compounds were highly toxic to S. zeamais by fumigation. The time required to cause 50% mortality of the pest was 28.4 hours on average, ranging from 17.3 to 40.8 hours between treatments. The toxic action of carvacrol, thymol and EOs of L. gracilis (no irrigation/fertilization mineral and 40 t ha-1 organic fertilizer) were the fastest, LT50=18,3. The magnitude of the variation of CL50 and CL99 were 1.9 and 2.1 times. The concentration needed to cause 50 to 99% mortality of the pest was on average 69 and 260 ìl l-1, respectively.Considering the LC50 and LC99, the more toxic OEs of L. gracilis were obtained from plants grown in the absence of mineral fertilizer and in the presence of organic manure with of 20, 40 and 60 t ha-1 (no irrigation) and 40 and 60 t ha-1 (with irrigation). Much of the activity of the EOs of L. gracilis is due to the major compound carvacrol. It took only 27.2 and 92.2 l ìl l-1 to cause 50% and 99 % mortality of adult S. zeamais. The toxic activity of this monoterpene was still one of the fastest (LT50 = 17.3 and LT99 = 70.8 hours). Already the thymol and ñ-cymene awere compounds of low toxicity to adult S. zeamais (LC50= 4,4 e 26,1 respectively). Generally, the EOs of L. gracilis and the monoterpenes applied at lower concentrations (0.01 and 0.1% v/v) showed a neutral effect (not significant) or attractive (negative and significant) in all periods analyzed. At concentration 10% (v/v) almost all treatments were repellents to S. zeamais at any time analyzed (repellence > 50%). Major indexes repellency (54-86%) were observed in treatments irrigated and with maximum organic manure, at concentrations of 1 and 10% (v/v). Thus, our results show the great potential of EO of L. gracilis and its major compound for the development of new products and programs for use in integrated pest management of stored grain.